Monoclonal B-cell lymphocytosis in a hospital-based UK population and a rural Ugandan population: a cross-sectional study. Issue 7 (July 2017) - Rawstron, Andy C; Ssemaganda, Aloysius; de Tute, Ruth; Doughty, Chi; Newton, Darren; Vardi, Anna; Evans, Paul A S; Stamatopoulos, Kostas; Owen, Roger G; Lightfoot, Tracy; Wakeham, Katie; Karabarinde, Alex; et al.
Summary: Background: Reported incidence of B-cell malignancies shows substantial geographical variation, being more common in the Americas and Europe than in Africa. This variation might reflect differences in diagnostic capability, inherited susceptibility, and infectious exposures. Monoclonal B-cell lymphocytosis (MBL) is a precursor lesion that can be screened for in apparently healthy people, allowing comparison of prevalence across different populations independently of health-care provision. We aimed to compare the prevalence and phenotypic characteristics of MBL in age-and-sex-matched populations from rural Uganda and the UK. Methods: In this cross-sectional study, we recruited volunteers aged at least 45 years who were seronegative for HIV-1 from the established Ugandan General Population Cohort and obtained their whole-blood samples. We also obtained blood samples from anonymised waste material of age-and-sex-matched individuals (aged >45 years, with a normal blood count and no history of cancer) in the UK. We used flow cytometry to determine the presence of MBL, defined according to standard diagnostic criteria, in the samples and compared differences in the proportion of cases with chronic lymphocytic leukaemia (CLL)-phenotype MBL and CD5-negative MBL, as well as differences in absolute monoclonal B-cell count between the two cohorts. Findings: Between Jan 15 and Dec 18, 2012, we obtained samples from 302 Ugandan volunteers and 302 UK individuals who were matched by age and sex to the Ugandan population. Overall MBL prevalence was higher in the Ugandan participants (42 [14%] individuals) than in the UK cohort (25 [8%]; p=0·038). CLL-phenotype MBL was detected in three (1%) Ugandan participants and 21 (7%) UK participants (p=0·00021); all three Ugandan participants had absolute monoclonal B-cell count below one cell per μL, whereas the 21 UK participants had a median absolute number of circulating neoplastic cells of 4·6 (IQR 2–12) cells per μL. The prevalence of CD5-negative MBL was higher in the Ugandan cohort (41 [14%], of whom two [5%] also had CLL-phenotype MBL) than in the UK cohort (six [2%], of whom two [33%] also had CLL-phenotype MBL; p<0·0001), but the median absolute B-cell count was similar (227 [IQR 152–345] cells per μL in the Ugandan cohort vs 135 [105–177] cells per μL in the UK cohort; p=0·13). Interpretation: MBL is common in both Uganda and the UK, but the substantial phenotypic differences might reflect fundamental differences in the pathogenesis of B-cell lymphoproliferative disorders. Funding: UK Medical Research Council and UK Department for International Development.